The Impact of Teachers' Professional Competence and Students' Emotional Intelligence on Arabic Learning achievements at Madrasah Aliyah Negeri 1 in Palembang - Yusnani; Munirul Abidin; Penny Respati Yurisa (Tarling : Journal of Language Education, 2025)
This research aims to determine the impact of teachers’ professional competence and students’ emotional intelligence on Arabic language learning achievement at Madrasah Aliyah Negeri 1 Palembang. This research employed quantitative methods with a survey research design. The population included all students at Madrasah Aliyah Negeri 1 Palembang. A stratified random sampling technique was utilized, yielding a research sample of 91 students. Data were obtained through questionnaires and supporting documents. The findings of this study demonstrate that both independent variables—teachers' professional competence and students' emotional intelligence—positively and significantly impact Arabic learning achievements. The regression coefficient for teachers' professional competence is 0,101, while for students' emotional intelligence, it is 0,086. Furthermore, hypothesis testing using the F-test revealed that the F-count exceeds the F-table (8,635 > 3,10), with a significance coefficient of 0.000 which is below 0.05. This shows that the hypothesis (Ha) is accepted which states that teachers‘ professional competence and students’ emotional intelligence together have a significant effect on Arabic learning achievement.